#TITLE_ALTERNATIVE# - ANDROSS (NIM. 15107062); Pembimbing: Prof. Dr. Ir. Ketut Wikantika, M.Eng., dan Dr. Ir. Kosasih, TRIO
Remote sensing has been frequently used in population estimation. This research developed a method to estimate the population of Bandung City using Landsat 7 ETM+ imagery and the population data from each district of Bandung City. The spectral bands of imagery, vegetation indices, and temperature of each district becomes independent variables to estimate the population density as the dependent variable. Linear regression analysis used to determine the correlation between the two variables and develop mathematical equations where population density is a function of the independent variables. Mathematical equations to estimate the population density of Bandung City become better in terms of accuracy and reliability, composed by several independent variables, namely vegetation index, spectral band images, and temperature. The obtained result of population estimation of Bandung City in 2003 with an error rate below 8%.